Integrative Network Pharmacology Study of Cordyceps militaris Compounds for Prostate Cancer Treatment - Laihad, Sarah Cecilia Astrid; Tallei , Trina Ekawati; Tendean , Lydia Estelina Naomi; Turalaki, Grace Lendawati Amelia; Marunduh, Sylvia Ritta; Purwanto , Diana Shintawati; Kepel, Billy Johnson; Abas, Abdul Hawil (Heca Sentra Analitika, 2026)
Prostate cancer remains one of the leading causes of cancer-related mortality in men, while adverse effects and the development of drug resistance often limit current therapeutic strategies. Natural products have gained increasing attention as potential sources of novel anticancer agents due to their multitarget properties and relatively low toxicity. Cordyceps militaris, a medicinal fungus rich in bioactive compounds, has been reported to exhibit anticancer activity; however, its compound-target interactions in prostate cancer have not been comprehensively elucidated. This study aimed to explore the interactions between C. militaris bioactive compounds and prostate cancer-associated targets using a pharmacology network-based in silico approach. A total of 50 bioactive compounds were collected from metabolite profiling studies, of which 19 compounds were selected based on high predicted TP53 expression enhancer activity (Pa ≥ 0.7) using WAY2DRUG PASS analysis. Protein targets were predicted using SwissTargetPrediction and the Similarity Ensemble Approach, and then intersected with prostate cancer-associated proteins retrieved from GEPIA2, GeneCards, and OMIM, yielding 499 overlapping targets. Protein interaction network analysis was performed using STRING and visualized in Cytoscape, enabling the identification of key hub proteins based on the applied parameters, highlighting ten key proteins, including SRC, ESR1, MAPK1, AKT1, HSP90AA1, MAPK3, HSP90AB1, EGFR, GRB2, and PRKACA, within the interaction network. Pathway enrichment analysis indicated that these targets were predominantly involved in cancer-associated signaling pathways, such as the EGFR tyrosine kinase inhibitor resistance pathway. Furthermore, the results revealed that the selected compounds interact with these key prostate cancer-associated proteins. Pharmacokinetic and toxicity evaluation predicted favorable drug-likeness and acceptable safety profiles for selected compounds. Overall, this study highlights the potential of C. militaris bioactive compounds as promising alternative for prostate cancer through multitarget modulation of clinically relevant signaling pathways. Further experimental validation is still required to confirm these findings.